Complications and 30-day Outcomes Associated With Venous Thromboembolism in the Pediatric Orthopaedic Surgical Population. Issue 3 (March 2016) - Baker, Dustin; Sherrod, Brandon; McGwin, Gerald; Ponce, Brent; Gilbert, Shawn
Abstract : Introduction: The risk of morbidity associated with venous thromboembolism (VTE) after pediatric orthopaedic surgery remains unclear despite increased use of thromboprophylaxis measures. Methods: The American College of Surgeons National Surgical Quality Improvement Program, Pediatric database was queried for patients undergoing an orthopaedic surgical procedure between 2012 and 2013. Upper extremity and skin/subcutaneous surgeries were excluded. Associations between VTE and procedure, demographics, comorbidities, preoperative laboratory values, and 30-day postoperative outcomes were evaluated. Results: Of 14, 776 cases, 15 patients (0.10%) experienced postoperative VTE. Deep vein thrombosis (DVT) occurred in 13 patients (0.09%), and pulmonary embolism developed in 2 patients (0.01%). The procedure with the highest VTE rate was surgery for infection (1.2%). Patient factors associated with the development of VTE included hyponatremia ( P = 0.003), abnormal partial thromboplastin time ( P = 0.046), elevated aspartate transaminase level ( P = 0.004), and gastrointestinal ( P = 0.011), renal ( P = 0.016), and hematologic ( P = 0.019) disorders. Nearly half (46.2%) of DVTs occurred postdischarge. Complications associated with VTE included prolonged hospitalization ( P < 0.001), pneumonia ( P < 0.001), unplanned intubation ( P = 0.003), urinary tract infection ( P = 0.003), and central line-associated bloodstream infection ( P < 0.001). Most of the postoperative complications (66.7%) occurred before VTE diagnosis, and no patients with VTE died. Conclusion: In the absence of specified risk factors, thromboprophylaxis may be unnecessary for this population.